Pianeta Nutrizione kids: international pediatric conference on food, physical activity, growth and well-being. Issue 1 (June 2016) - Agosti, Massimo; Agostoni, Carlo; Chalons, Serge; Chavatte-Palmer, Pascale; Villares, José; Nicklaus, Sophie; Pereira-da-Silva, Luís; Pietrobelli, Angelo; Rolland-Cachera, Marie; Zuccotti, Gian; Cappa, Marco; Caruso-Nicoletti, Manuela; et al.
Table of contents A1 Preterm and low birth weight nutrition in the first month life: implications for the outcome Massimo Agosti A2 Behind human milk and breastfeeding: not only food, not only growth Carlo Agostoni A3 To prevent obesity: importance and issues of cultural adaptation from weaning to 3 years of age Serge Chalons A4 Diet before and during pregnancy and child health: lessons from animal models Pascale Chavatte-Palmer A5 Infant nutrition: an opportunity to optimize future health José Manuel Moreno Villares A6 Complementary feeding strategies to facilitate acceptance of fruits and vegetables Sophie Nicklaus A7 Diet of young children in the Mediterranean region Luís Pereira-da-Silva A8 Proposal of 10 good practices to help prevent obesity in the first 1, 000 days Angelo Pietrobelli, the MeNu Group A9 Macronutrient intakes in early life and subsequent risk of obesity Marie Françoise Rolland-Cachera A10 The burden of childhood obesity in Italy and the results of Nutrintake study Gian Vincenzo Zuccotti A11 Growth body composition and growth hormone therapy: linear growth Marco Cappa A12 Early nutrition pattern and late metabolic consequences Manuela Caruso-Nicoletti A13 Nutrition and Insulin-like Growth Factor (IGF) System Elena Inzaghi, Stefano Cianfarani A14 Nutrition of preterm infants Mario De Curtis A15 Early nutrition patterns and later metabolic outcomes- I part: Genetic and metabolic mechanisms Laura Guazzarotti A16 Diagnosis of metabolic disease by imaging techniques Lorenzo Iughetti A17 Nutrition, growth and cardiovascular diseases Francesco Chiarelli, Laura Comegna, Simone Franchini A18 Body fat mass and gender Laura Perrone, Giuseppina Rosaria Umano A19 Lifestyle interventions for an appropriate birth weight Elisabetta Petrella, Raffaele Bruno, Valentina Bertarini, Giulia Pedrielli, Isabella Neri, Fabio Facchinetti A20 Nutrition, growth and body composition Flavia Prodam A21 Nation-specific reference growth charts in the daily practice Alessandro Sartorio, John M. H. Buckler, Nicoletta Marazzi A22 Growth patterns in inflammatory bowel diseases (IBD) and in cystic fibrosis (CF) Maria E. Street, Viviana D. Patianna, Paola Accorsi, Sara Lo Scocco, Sergio Amarri A23 Newborn in the digital era and their body feeling: physical exercise to counteract hyperphagia Alberto Pellai A24 Nutrition, young athletes and effects of exercise. Practical suggestions Giampiero Merati A25 Physical exercise as a way to prevent criminality in minors and teenagers Isabella Merzagora A26 The measurement of daily energy expenditure in children. Evaluation of a new wrist portable device vs breath-by-breath metabolimeter Susanna Rampichini, Arsenio Veicsteinas A27 Probiotic and inflammasomes Mario Clerici A28 Probiotics and newborns Paolo Manzoni, Elena Tavella, Elena Boano, Daniele Farina A29 Relationship between gut microbiota and obesity Fabio Pace